What is happening with Obstetric Fistula in the West of Nepal? - Heywood, Shirley (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Analyzing the changes in the characteristics of patients presenting with fistula in Surkhet. The impact of births after the development of fistula on the grade of fistula and outcome is examined. Methods: This study examines the records of 282 fistula patients identified in Surkhet between 2009 and 2018. Results: There has been reduction in number of women presenting with the most complex vesico-vaginal fistulae and reduction in average number of years women have lived with obstetric fistula before treatment. More women present within one year of injury and better outcome is seen in those with more recent injury. A moderate increase in patients presenting with iatrogenic fistula is seen, (2011 obstetric fistula 77%, iatrogenic 6%, 2018 obstetric fistula 68.5%, iatrogenic 17%). Conclusions: The findings suggest that easier access to maternity care and better fistula awareness is reducing the occurrence of the most severe injuries and improving outcomes.